Die Haut des Satyrs: Marsyas und Apollo - Darab , Ágnes (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The essay proceeds from the observation that out of the surviving literature of antiquity only one poet, Ovid pays significant attention to the tragic fate of Marsyas. Both the Fasti and the Metamorphoses relate the tale. The narrative in Metamorphoses only focuses on the naturalistic description of the punishment, the flaying of Marsyas. The interpretation of this account within even wider contexts leads to the proposition that Marsyas’s tale is the self-reflection of the elegiac poet Ovid, and as such it becomes a key narrative within Metamorphoses.